Electrostatic Solitary Waves in the Earth's Bow Shock: Nature, Properties, Lifetimes, and Origin. Issue 7 (2nd July 2021) - Wang, R.; Vasko, I. Y.; Mozer, F. S.; Bale, S. D.; Kuzichev, I. V.; Artemyev, A. V.; Steinvall, K.; Ergun, R.; Giles, B.; Khotyaintsev, Y.; Lindqvist, P.‐A.; Russell, C. T.; et al.
Abstract: We present a statistical analysis of >2, 100 bipolar electrostatic solitary waves (ESWs) collected from 10 quasi‐perpendicular Earth's bow shock crossings by Magnetospheric Multiscale spacecraft. We developed and implemented a correction procedure for reconstruction of actual electric fields, velocities, and other properties of ESW, whose spatial scales are typically comparable with or smaller than spatial distance between voltage‐sensitive probes. We found that more than 95% of the ESW are of negative polarity with amplitudes typically below a few Volts and 0.1 T e (5–30 V or 0.1–0.3 T e for a few percent of ESW), spatial scales of 10–100 m or λ D –10 λ D, and velocities from a few tens to a few hundred km/s that is on the order of local ion‐acoustic speed. The spatial scales of ESW are correlated with local Debye length λ D . The ESW have electric fields generally oblique to magnetic field and they propagate highly oblique to shock normal N ; more than 80% of ESW propagate within 30° of the shock plane LM . In the shock plane, ESW typically propagates within a few tens of degrees of local magnetic field projection B LM and preferentially opposite to N  × B LM . We argue that the ESW of negative polarity are ion holes produced by ion‐ion streaming instabilities. We estimate ion hole lifetimes to be 10–100 ms, or 1–10 km in terms of traveling distance. The revealed statistical properties will be useful for quantitative studies of electron thermalization in the Earth's bow shock. Plain Language Summary: The Earth's bow shock is a natural laboratory for in‐situ analysis of plasma processes in supercritical collisionless shock waves. The current consensus is that quasi‐static magnetic and electric fields play a major role in electron heating, while scattering by waves results in thermalization of electron velocity distribution functions shaped by quasi‐static fields. Among various waves observed in the Earth's bow shock, electrostatic fluctuations deserve particular attention, because they are always present in the shock transition region. This study is focused on experimental analysis of electrostatic fluctuations in the Earth's bow shock using 3D electric field measurements by the Magnetospheric Multiscale (MMS) spacecraft. We presented a statistical analysis of electrostatic solitary waves (ESWs) using a data set of more than 2, 000 solitary waves selected in 10 Earth's bow shock crossings. In contrast to previous interpretations, we showed that ESWs in the Earth's bow shock are predominantly ion phase‐space holes, which is a strong indication that electrostatic fluctuations in the Earth's bow shock are produced by ion‐ion streaming instabilities. We obtained statistical distributions of various properties of ion holes, which will be of value for quantifying electron thermalization by electrostatic fluctuations in collisionless shocks. Key Points: More than 95% of bipolar electrostatic structures in the Earth's bow shock are ion holes Ion holes typically have electric fields oriented oblique to local magnetic field We estimated lifetimes of ion holes to be 10–100 ms or 1–10 km in terms of traveling distance